2020
DOI: 10.1186/s12917-020-2232-y
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on molecular diagnosis of Hapalotrema mistroides (Digenea: Spirorchiidae) infection in blood samples of live loggerhead turtles Caretta caretta

Abstract: Background: Parasites of the family Spirorchiidae cause disease and mortality in marine and freshwater turtles; two species, Hapalotrema mistroides and Neospirorchis sp., are reported in the resident population of loggerhead turtles of the Mediterranean Sea, with the first being the most widespread. In vivo diagnosis of spirorchidiasis can represent a challenge in guaranteeing prompt control and treatment of the disease and is currently limited to copromicroscopy. The aim of this study was the development of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Several species of sea turtles have been affected in various ocean basins. Severe fluke lesions have been reported in Florida (13,14), Hawaii (15), Costa Rica (16,17), Brazil (18,19), and Italy (12,20), with Australia experiencing the highest prevalence and greatest mortality rates (21)(22)(23). This study reports the first case of Learedius learedi infection associated with bilateral blindness in a green sea turtle of the Northern Red Sea.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Several species of sea turtles have been affected in various ocean basins. Severe fluke lesions have been reported in Florida (13,14), Hawaii (15), Costa Rica (16,17), Brazil (18,19), and Italy (12,20), with Australia experiencing the highest prevalence and greatest mortality rates (21)(22)(23). This study reports the first case of Learedius learedi infection associated with bilateral blindness in a green sea turtle of the Northern Red Sea.…”
Section: Introductionmentioning
confidence: 76%
“…To date, the standard way to diagnose these parasites in live animals is based on the morphology of the eggs by copro-microscopy examination (10). However, in 2020, Marchiori et al demonstrated the need for more accurate methodologies and consequently developed a blood sample analysis method that provides improved precision (12).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, the lack of reliable ante‐mortem diagnostic techniques to detect spirorchiid fluke infection has prevented an accurate determination of the true prevalence and morbidity of disease caused by the parasite 35 . Recent advances have succeeded in using molecular tools such as polymerase chain reactions to detect parasite DNA 36 ; however, direct ultrasonographical examination of the heart and major arteries, which is a site commonly inhabited by these parasites 33 , may enable real‐time, in‐field diagnosis of this disease. Combining this technique with traditional health assessments such as haematological and biochemical analyses, body condition metrics 2 and novel biomarkers capable of quantifying thromboembolic disease may improve the ability of researchers to monitor the health of wild populations and aid clinicians in the development of treatment protocols in animals undergoing rehabilitation.…”
Section: Discussionmentioning
confidence: 99%